Maculopathy and adult‐onset ataxia in patients with biallelic MFSD8 variants - Sigurd Dobloug; Ulrika Kjellström; Glenn Anderson; Emily Gardner; Sara E. Mole; Jayesh Sheth; Andreas Puschmann (Molecular Genetics & Genomic Medicine)
Abstract Background Biallelic variants in the major facilitator superfamily domain containing 8 gene (MFSD8) are associated with distinct clinical presentations that range from typical late‐infantile neuronal ceroid lipofuscinosis type 7 (CLN7 disease) to isolated adult‐onset retinal dystrophy. Classic late‐infantile CLN7 disease is a severe, rare neurological disorder with an age of onset typically between 2 and 6 years, presenting with seizures and/or cognitive regression. Its clinical course is progressive, leading to premature death, and often includes visual loss due to severe retinal dystrophy. In rare cases, pathogenic variants in MFSD8 can be associated with isolated non‐syndromic macular dystrophy with variable age at onset, in which the disease process predominantly or exclusively affects the cones of the macula and where there are no neurological or neuropsychiatric manifestations. Methods Here we present longitudinal studies on four adult‐onset patients who were biallelic for four MFSD8 variants. Results Two unrelated patients who presented with adult‐onset ataxia and had macular dystrophy on examination were homozygous for a novel variant in MFSD8 NM_152778.4: c.935T>C p.(Ile312Thr). Two other patients presented in adulthood with visual symptoms, and one of these developed mild to moderate cerebellar ataxia years after the onset of visual symptoms. Conclusions Our observations expand the knowledge on biallelic pathogenic MFSD8 variants and confirm that these are associated with a spectrum of more heterogeneous clinical phenotypes. In MFSD8‐related disease, adult‐onset recessive ataxia can be the presenting manifestation or may occur in combination with retinal dystrophy.